Paracrine potential of adipose stromal vascular fraction cells to recover hypoxia‐induced loss of cardiomyocyte function. Issue 1 (27th October 2018) - Mytsyk, Myroslava; Isu, Giuseppe; Cerino, Giulia; Grapow, Martin T. R.; Eckstein, Friedrich S.; Marsano, Anna
Abstract: Cell‐based therapies show promising results in cardiac function recovery mostly through paracrine‐mediated processes (as angiogenesis) in chronic ischemia. In this study, we aim to develop a 2D (two‐dimensional) in vitro cardiac hypoxia model mimicking severe cardiac ischemia to specifically investigate the prosurvival paracrine effects of adipose tissue‐derived stromal vascular fraction (SVF) cell secretome released upon three‐dimensional (3D) culture. For the 2D‐cardiac hypoxia model, neonatal rat cardiomyocytes (CM) were cultured for 5 days at < 1% (approaching anoxia) oxygen (O2 ) tension. Typical cardiac differentiation hallmarks and contractile ability were used to assess both the cardiomyocyte loss of functionality upon anoxia exposure and its possible recovery following the 5‐day‐treatment with SVF‐conditioned media (collected following 6‐day‐perfusion‐based culture on collagen scaffolds in either normoxia or approaching anoxia). The culture at < 1% O2 for 5 days mimicked the reversible condition of hibernating myocardium with still living and poorly contractile CM (reversible state). Only SVF‐medium conditioned in normoxia expressing a high level of the prosurvival hepatocyte‐growth factor (HGF) and insulin‐like growth factor (IGF) allowed the partial recovery of the functionality of damaged CM. The secretome generated by SVF‐engineered tissues showed a high paracrine potential to rescue the nonfunctional CM, therefore resulting in a promising patch‐based treatment of specific low‐perfused areas after myocardial infarction. Abstract : Cell‐based therapies show promising results in cardiac function recovery mostly through paracrine‐mediated processes (as angiogenesis) in chronic ischemia. In this study, we aim to develop a 2D (two‐dimensional) in vitro cardiac hypoxia model mimicking severe cardiac ischemia to specifically investigate the prosurvival paracrine effects of adipose tissue‐derived stromal vascular fraction (SVF) cell secretome released upon three‐dimensional (3D) culture.